2014
DOI: 10.1517/13543776.2014.995628
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel blockers: a patent review (2010 – 2014)

Abstract: Over the past 4 years we assisted to a continuous effort in the discovery of new sodium channel blockers by a large number of pharmaceutical companies. All the different chemical classes presented, and here analyzed, could represent an important breakout but, the lack of precise structural information, with the incompleteness of the biological data hampered the possibility to understand the real 'state of the art' of any of these inventions. Upon analysis of a number of patents in this review, it remains clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…McCormack and colleagues (2013) demonstrated that interaction with three amino acid residues on the extracellular facing S2 and S3 transmembrane segments of the Domain 4 voltage sensor was important for both activity and selectivity for both Na v 1.7 and Na v 1.3 selective members of an aryl sulfonamide class of Na v channel inhibitors. To better understand the structure-activity relationships underlying this subtype selective interaction, additional aryl sulfonamide and structurally related agents have been generated and characterized (Bagal et al, 2014;Zuliani et al, 2015). During these efforts, two compounds (PF-05661014 and PF-06526290), which differ only by a methyl moiety, have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…McCormack and colleagues (2013) demonstrated that interaction with three amino acid residues on the extracellular facing S2 and S3 transmembrane segments of the Domain 4 voltage sensor was important for both activity and selectivity for both Na v 1.7 and Na v 1.3 selective members of an aryl sulfonamide class of Na v channel inhibitors. To better understand the structure-activity relationships underlying this subtype selective interaction, additional aryl sulfonamide and structurally related agents have been generated and characterized (Bagal et al, 2014;Zuliani et al, 2015). During these efforts, two compounds (PF-05661014 and PF-06526290), which differ only by a methyl moiety, have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…59 In concert, therapeutic molecules that block specific subtypes of sodium channels while sparing others are under development. 60 Advanced techniques for atomic-level molecular modelling, 61 together with the solution of the crystal structure of prototypical bacterial sodium channels, have propelled molecular pharmacology to new levels.…”
Section: Channelopathies Stephen G Waxmanmentioning
confidence: 99%
“…Auf Einzelfallebene spielen Polymorphismen diagnostisch bisher keine bedeutende Rolle, jedoch könnte ihnen in Zukunft eine wichtige Funktion zukommen, wenn es darum geht, anhand von Fehlregulationen bestimmter Systeme eine "maßgeschneiderte" Therapie für Patienten zu planen. Selektiv auf Nav1.7-Kanäle wirkende Pharmaka sind seit Langem in der Entwicklung [42][43][44], jedoch ist diese nicht unproblematisch, da es schwierig zu sein scheint, Substanzen mit hoher Selektivität herzustellen [45].…”
Section: Spannungsabhängige Natriumkanäle Und Small-fiber-neuropathieunclassified